Hydrodynamics of Superparamagnetic Iron Oxide Nanoparticles. (2017) - Vikram, S.; Vasanthakumari, R.; Tsuzuki, Takuya; Rangarajan, Murali
Abstract: Superparamagnetic iron oxide nanoparticles have found particular interest in magnetic drug targeting, hyperthermia, and magnetophoresis, where their flow behavior in the presence and absence of magnetic field is of particular interest. Magnetite nanoparticles of diameter 6.5 nm have been synthesized by co-precipitation of Fe 2+ and Fe 3+ ions at room temperature. They exhibit high magnetization (∼ 70-75 emu/g) even when chelated with citric acid. Hydrodynamics of these nanoparticles has been studied in water medium at flow rates similar to those observed in blood vessels under the influence of different magnetic fields up to 0.5 Tesla and at different distances from the tube wall. An experimental setup has been fabricated in-house comprising a straight test section, a peristaltic pump for pumping water, a permanent magnet mounted at different distances from the test section, and a CMOS camera mounted 90 degrees from the magnet to image the nanoparticles under the influence of magnetic and flow fields. The observed time-lapse images indicate that in the absence of an external magnetic field, the magnetic interactions between the nanoparticles are not strong enough to withstand the normal and shear forces arising from flow. Thus, most of the particles get washed away. Chelating the nanoparticles with citric acid disperses the nanoparticles more effectively, and also aid in flow of the nanoparticles away from the region of visualization. On the other, in the presence of a magnetic field, most of the nanoparticles are attracted to the wall of the tube closest to the magnet and are retained for longer durations. Yet, it is also seen that the hydrodynamic forces are able to gradually remove the retained nanoparticles. The developed setup is an effective means to study the hydrodynamics of iron oxide nanoparticles, particularly in relevance to emerging applications.